Surface dissolution and amorphization of electrocatalysts during oxygen evolution reaction: Atomistic features and viewpoints. (September 2022) - Yun, Tae Gyu; Sim, Yelyn; Lim, Younghwan; Kim, Dongho; An, Ji-Sang; Lee, Hyungdoh; Du, Yingge; Chung, Sung-Yoon
Graphical abstract: Abstract: Electrochemical electrolysis with an aqueous electrolyte is a key method to obtain green hydrogen energy, convert carbon dioxide into high value-added carbon-based chemicals, and produce ammonia by nitrogen reduction at ambient conditions. For better efficiency of these electrolysis processes, lowering the comparatively large activation barrier of the sluggish oxygen evolution reaction (OER) at the anode side is necessary. Therefore, suitable electrocatalysts should be adopted to facilitate the OER. As a highly oxidizing environment along with high overpotential is unavoidable at the anode during electrolysis, degradation of both the activity and durability of OER catalysts inevitably takes place. In this Review, we classify four significant origins directly affecting the stability of oxide-based OER catalysts: (1) Alkali and alkaline-earth metal dissolution; (2) transition-metal leaching; (3) lattice oxygen evolution; and (4) rapid dissolution of phosphorus and chalcogens. In particular, because these origins usually induce amorphization or reconstruction at the surface, we systematically summarize atomic-level evidence largely based on transmission electron microscopy in each section. Providing integrated viewpoints for a better understanding of catalyst degradation, we believe that this Review offers valuable insight toward designing new OER catalysts with enhanced durability and activity.